Determination of Potential Zones for Website-Based Small Pelagic Fish in Banten Bay Waters - Ayang Armelita Rosalia; Denta Tirtana; Luthfi Anzani; Amanda Chairunnisa; Naufal Rahaditya Aryadi; Adela Nur Anbiya; Anggieta Tri Cahyani; Batrisya Hawani Balqis; Mahathir Muhamad Ashari; Muhamad Rifky Rivandi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The waters of Banten Bay have abundant resources of small pelagic fish. Anchovies, mackerel, Shortfin scad, goldstripe sardinella, selar fish, mullet, and lemuru are small types of pelagic fish that can be found all year round in the waters of Banten Bay. Based on its abundant potential, however, its utilization is still inefficient because most local fishermen still use traditional fishing methods, which result in low catches and incomes. The purpose of this study is to develop a website-based system to determine the Fishing Potential Zone (FPZ) in the waters of Banten Bay by utilizing sea surface temperature (SST) and chlorophyll-a data from Aqua MODIS satellite imagery in 2023. Data processing is carried out with SeaDAS and ArcGIS software to determine FPZ points that are implemented in the form of a website, namely FishZone Mapper. The FishZone Mapper website is designed to provide information that can be easily accessed by fishermen, researchers, and other stakeholders to improve fishing efficiency. The results showed that there was a significant difference in the number of FPZ points in the western and eastern seasons, which affected fishing strategies.